Evaluasi Faktor-Faktor Yang Mempengaruhi Performa Implementasi SAP ERP Di Industri Retail - Bakhri, Syaiful (Universitas Islam Negeri Walisongo Semarang, 2019)
This study aims to examine the factors that affect the performance of the ERP implementation. These factors are: the data migration, system documentation, knowledge transfer, system testing, and integration interfaces. These factors can increase the performance of the implementation of ERP software applications that are on retail industry. The case study method in this research is using interviews and direct observation, the object of the interview in this study is Functional modules of SAP ERP. Sources of data derived from primary data and secondary data. The results of this study indicate that factors influence on the performance of retail industry. Therefore, the factors to be considered in order to improve the success of SAP ERP project in the future. The theoretical implications and suggestions for future research are also discussed in the final part of this study. (SB)